Evaluation System Information Service Letter Village Use Usability Scale System - Khotnai Shinta; Raissa Amanda Putri (Jurnal Mantik, 2022)
System _ service letter in village Siundol Jae already using information systems service Web-based. However use the system still not enough effective because a lot obstacles, such as lack of understanding government Village in use of computers, limited computers in the village, and lack of interest government Village for use the service system letter Web-based. The process used for system evaluation that is observation and literacy, formulation problems, evaluation, data collection, data analysis, conclusions and suggestions. Method used that is method Scale usability system.So expected with existence evaluation the use of information systems service letter in village Siundol Jae will more efficient. So that government Village will more easy in serve needs letter correspondence in the village Siundol Jae dan Public also will more satisfied to service the letter that was given government Village.